The majority of irregular menstrual cycles in adolescence are ovulatory: Results of a prospective study - Peña, A.; Doherty, D.; Atkinson, Helen; Hickey, M.; Norman, R.; Hart, R. (BMJ Group, 2018)
Purpose: While ovulation is most likely to occur in adolescent girls with regular menstrual cycles, there are limited data on the incidence of ovulation in girls with irregular menstrual cycles in early postmenarcheal years. The aim of the study was to evaluate the presence of ovulation in healthy postmenarcheal girls with irregular menstrual cycles. Methods, design and subjects: Prospective cohort study over 12 weeks including 40 healthy postmenarcheal girls recruited from the population-based cohort of adolescents from Western Australian Pregnancy Cohort (Raine) Study with irregular menstrual cycles defined by either menstrual cycles <21 days or >35 days in duration or cycle length that varied from month to month by >4 days according to menstrual diaries. Main outcome measure: Ovulation defined by urinary pregnanediol-3α–glucuronide/creatinine measurements higher than three times above minimum value obtained from 12 samples (1 per week). Results: Forty girls (37 Caucasians) with irregular menstrual cycles aged 15.1 (median (IQR) 14.9–15.4) years who were 2.3 (1.9–3.3) years postmenarche were assessed. Urinary pregnanediol-3α–glucuronide/creatinine values identified that 33 girls (82.5%) ovulated during the 3 months of observation and 7 girls had anovulatory cycles. Menstrual diaries collected for a median (IQR) of 159 (137.5–188.2) days showed median minimal and maximum menstrual cycle duration of 24 (11.5–29) and 38.5 (35–48) days, respectively. Conclusions: A large proportion of healthy adolescent girls with irregular menstrual cycles are still ovulating despite irregular and infrequent menses.